1989
DOI: 10.1016/0014-5793(89)81495-4
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D activation by the mitogens platelet‐derived growth factor and 12‐O‐tetradecanoylphorbol 13‐acetate in NIH‐3T3 cells

Abstract: The effect of mitogens on phospholipase D activity was investigated in NIH-3T3 fibroblasts by measuring the accumulation of phosphatidylpropan-01, produced by phospholipase D phosphatidyl transferase activity when I-propanol acts as the phosphatidyl group acceptor. Platelet-derived growth factor (PDGF) and 120tetradecanoylphorbol13-acetate (TPA) stimulated phosphatidylpropanol production by the cells. The dose-response relationships for activation of phospholipase D and stimulation of thymidine incorporation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 18 publications
2
28
0
1
Order By: Relevance
“…Despite lack of precise knowledge about PLD regulation, a great deal of evidence indicates that mammalian PLDs have a role in signal transduction (Frohman and Morris, 1996;Hammond et al, 1995). Phospholipase D is activated after stimulation with growth factors (Ben-Av and Liscovitch, 1989;Kiss, 1992), hormones (Freeman and Tallant, 1994; Kiss et al, 1991;Liscovitch and Amsterdam, 1989;Qian and Drewes, 1989) and phorbol esters (del Peso et al, 1996(del Peso et al, , 1997Huang and Cabot, 1990). PLD added exogenously to cells has mitogenic activity, and its activation has been implicated in the transduction of several stimuli and the regulation of diverse biological processes including cell growth and metastasis (Bonser et al, 1989;Carnero and Lacal, 1995;Imamura, et al, 1993;Kondo et al, 1992;Liscovitch and Amsterdam, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Despite lack of precise knowledge about PLD regulation, a great deal of evidence indicates that mammalian PLDs have a role in signal transduction (Frohman and Morris, 1996;Hammond et al, 1995). Phospholipase D is activated after stimulation with growth factors (Ben-Av and Liscovitch, 1989;Kiss, 1992), hormones (Freeman and Tallant, 1994; Kiss et al, 1991;Liscovitch and Amsterdam, 1989;Qian and Drewes, 1989) and phorbol esters (del Peso et al, 1996(del Peso et al, , 1997Huang and Cabot, 1990). PLD added exogenously to cells has mitogenic activity, and its activation has been implicated in the transduction of several stimuli and the regulation of diverse biological processes including cell growth and metastasis (Bonser et al, 1989;Carnero and Lacal, 1995;Imamura, et al, 1993;Kondo et al, 1992;Liscovitch and Amsterdam, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine kinase receptors such as epidermal growth factor (EGF) and platelet-derived growth factor receptors stimulate PLD activity in some cell types, suggesting that PLD activity is modulated by tyrosine phosphorylation (2,13,18). Recently, Min et al (33) and Marcil et al (31) reported that pervanadate induced tyrosine phosphorylation on PLD1 in Swiss 3T3 fibroblasts and HL60 cells, respectively.…”
mentioning
confidence: 99%
“…H 2 O 2 has been reported to enhance tyrosine phosphorylation of the platelet-derived growth factor (PDGF) receptor, the epidermal growth factor receptor, Src kinase, and mitogen-activated protein kinase, leading to activation of gene expression including c-fos, c-myc, c-jun, NF-B, and AP-1 (12)(13)(14)(15)(16). Tyrosine phosphorylation has also been implicated in PLD activation mediated by epidermal growth factor (17), PDGF (18), pervanadate (19,20), fMet-Leu-Phe (21), and immunoglobulin E (22). Furthermore, inhibitors of protein-tyrosine phosphatases such as peroxides of vanadate stimulate PLD activity by G proteinindependent (19) and -dependent (23) mechanisms.…”
mentioning
confidence: 99%